1103 A SINGLE CENTER EXPERIENCE ON RIGHT VENTRICULAR VS. BIVENTRICULAR FAILURE ASSESSMENT GUIDED BY CMRI AND 3-D ECHOCARDIOGRAPHY. (15th December 2022) - Rosa Romano, Letizia; Curcio, Antonio; Cardia, Giada; Malizia, Biagio; Fiore, Davide; Pasceri, Eugenia; Indolfi, Ciro
Abstract: Background: Currently, echocardiography represents the first-line diagnostic test for risk stratification in myocardial dysfunctions, cardiomyopathies (CM) and valvular heart diseases. Three-dimensional (3D) echo imaging improves the accuracy of cardiac chamber volumes evaluation in complex cardiac anatomies and eliminates the need for geometric modelling as well as the errors caused by foreshortened views. On the other side, cardiac magnetic resonance imaging (CMRi) has limited availability and relative high costs, whereas it provides the most accurate and reproducible measurement of atrial, biventricular global and regional systolic function, and can detect myocardial oedema, fibrosis, infiltration, and perfusion defects. Moreover, fibrosis detection by late gadolinium enhancement (LGE) contributes to ventricular tachyarrhythmias (VT) risk stratification. Our experience considers the diagnostic and prognostic role of an integrated approach guided by CMRi and 3-D echocardiography in two different subtypes of arrhythmogenic cardiomyopathy (ACM). Methods: In December 2018, a sixty-six-year-old man, without familiar history of sudden cardiac death (SCD) or cardiomyopathies was admitted to emergency department for dyspnoea and chest pain. First ECG showed a VT with right bundle branch block morphology, rapidly cardioverted. In July 2019, a fifty-six-year-old woman, without family history of SCD or ACM, with previous sustained VT episode with right ventricular (RV) outflow tract pattern was admitted to our centre for further examinations. In both cases routine exams were carried out, and, in the suspicious of ACM, genetic tests, 3-D echo and CMRi were performed. Results: in the first case, 3-D echo showed hypo-akinesia of left ventricular posterior-lateral wall, reduced ejection fraction (EF) 40%; enlargement of right chambers (RV end-diastolic volume, EDV, 194 ml; RV end-systolic volume, ESV, 152 ml) with reduced indices of systolic function (TAPSE 13 mm; FAC 25%; RV S' 7 cm/s). CMRi showed global hypokinesia and free lateral wall bulging with RV EDV 235 ml; RV ESV 147 ml; RV EF 26% and reduced left ventricular EF 36%. In the second case, 3-D echo documented RV EDV 175 ml; RV ESV 64 ml with preserved systolic function (TAPSE 20 mm; FAC 47%; global longitudinal strain, GLS, -19%) and bulging of medio-distal free wall, normal EF 57%; GLS -22.7%. At CMRi there was evidence of slight RV dilatation (RV EDV 193 ml; RV ESV 88 ml) and hypokinetic, mildly-reduced global systolic function (EF 49%), images of LGE due to possible diffuse myocardial fibrosis of the free wall with morpho-functional anomalies of the RV. Both cases had negative genetic tests. ACM diagnosis was made according to Padua criteria, and programmed ventricular stimulation (sustained VT induction with hemodynamic instability) mandated cardioverter/defibrillator implantation in both cases. Conclusions: In our experience, an integrated approach guided by CMRi and 3-D echocardiography in subtypes of ACM plays a pivotal role for assessing diagnosis by refining disease characterization through additional parameters. The non-invasive high-risk stratification was confirmed by electrophysiologic studies. Further studies for prognostic correlation between CMRi/advanced echocardiography and arrhythmic phenotype are mandatory.